Türkiye'nin Turizm Gelişimi ve Eğilimler (Aviation, 2021)
Research suggests that the tourism industry, known to affect over sixty sectors, is a major source of income in our country, as in many other countries. Its contribution to close the deficit in the balance of payments and to alleviate unemployment as it is a labour-intensive sector, demonstrates its importance. Moreover, while enabling foreign currency inflow for the country, the fact that it achieves this with minimal import, places the tourism sector in a truly "national and domestic" sector position. For this reason, it has been declared as a "strategic sector" by the Presidency. Having knowledge on which markets Turkey is specialized or not specialized, in comparison to competing countries and examining the areas where it has a competitive advantage or disadvantage is important in terms of policies and regulations to be implemented by the local and central administration bodies, as well as determining the strategies and management approach involving the future of the sector. Within this scope, the sectoral development of tourism and hotel management and new trends in Turkey are examined in this book and with the shift-share analysis among Mediterranean countries, dynamics are addressed. In the context of tourism, whether other countries and Turkey are specialized, in which country markets, has been examined. Besides constituting a resource for researchers studying tourism dynamics and trends, this book is intended to guide tourism policy and strategy developers and local administrations.